2020
DOI: 10.1039/d0sc04183a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoryl- and phosphonium-bridged viologens as stable two- and three-electron acceptors for organic electrodes

Abstract: Two strongly electron-accepting viologens, including an intriguing tricationic species, are reported. The utility of the tricationic viologen for energy storage has been showcased via use as electrode in a proof-of-concept battery.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…The most-studied systems are the viologen (1,1′-disubstituted-4,4′-bipyridinium salts) and its derivatives, for which many experimental studies have shown intrinsic properties that make them excellent candidates for a series of technological applications [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most-studied systems are the viologen (1,1′-disubstituted-4,4′-bipyridinium salts) and its derivatives, for which many experimental studies have shown intrinsic properties that make them excellent candidates for a series of technological applications [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical point of view, the studies are scarcer and have concerned some viologen-like [57], dithiolodithiole and thiophene [58], thiophene−pyrrole-containing rings [59], borepins [60], poly-dioxythiophene [61], and methyl ketone [62] systems. It is also worth mentioning certain investigations in which experimental data are coupled to theoretical data, demonstrating how the two approaches can be combined to provide useful insights on these interesting processes [36,39,53,56,[63][64][65][66][67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, viologens and their derivatives as electron acceptor cations, which can undergo reversible redox reactions, have been explored for electrochemical energy storage. [ 31 , 32 , 33 ] In light of this, the approaches prompt us to construct ionic organic compounds consisting of both redox cations and anions which can undergo reversible multielectron redox reactions to improve their stability and theoretical capacity.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be synthesized with a variety of substituents at the nitrogen position that shift their molecular orbital energy levels. Fine-tuning possibilities of colors and redox properties have therefore led to applications in electrochromic devices, molecular machines, , and organic radical batteries. , …”
Section: Introductionmentioning
confidence: 99%
“…Finetuning possibilities of colors and redox properties have therefore led to applications in electrochromic devices, 13 molecular machines, 14,15 and organic radical batteries. 16,17 Solution phase viologens have been extensively characterized by UV−vis 18−20 and resonance Raman spectroscopies 21,22 due to their blue color and by electron paramagnetic resonance (EPR) due to their radical nature. 18,20,23 The dimer has an absorption in the near-infrared and is EPR silent which makes it easily distinguishable from the monomer form.…”
Section: ■ Introductionmentioning
confidence: 99%